Chinese EFL learners’ empowerment: does teacher care and confirmation matter? - Li, Min; Chu, Zhesen (Frontiers in Psychology, 2023)
Introduction: Inspired by the rhetorical/relational goal theory, the current inquiry evaluated the role of two teacher relational behaviors, namely care and confirmation, in predicting Chinese EFL learners’ empowerment. Methods: To do this, we administered three closed-ended scales to 391 Chinese students who studying English as a foreign language in various educational institutions in China. Students’ attitudes towards the interplay between teacher care, teacher confirmation, and learner empowerment were statistically analyzed using IBM SPSS Amos software. Results: The results uncovered that teacher confirmation and teacher care serve an essential role in improving Chinese EFL learners’ empowerment. This indicates that EFL learners’ empowerment strictly depends on the relational behaviors that teachers employ in instructional-learning contexts. Discussion: The study outcomes may have some theoretical and practical implications for L2 researchers, language teachers, and teacher trainers.